Examining transformational leadership, Work Environment and Job Satisfaction on Organizational Commitment: Employees PT. Pandungo Main Partner - Muhammad Dody Mesya Putra; Setia, Shinta (Profesional Muda Cendekia Publishing, 2024)
Research Aims: This research aims to examine the influence of Transformational Leadership, Work Environment, and Job Satisfaction on Organizational Commitment. Design/methodology/approach: the study employed a quantitative research approach. 32 workers at PT. Pandungo Main Partner served as the study's sample. The research employs a non-probability sampling technique for sampling. A Likert scale questionnaire distributed in accordance with suitable criteria is used as the data collection tool in this study. Utilizing partial least squares structural equation modeling for statistical analysis (PLS-SEM). Research Findings: The study's findings demonstrate the positive and substantial effects of job satisfaction, work environment, and transformational leadership style on organizational commitment. Employee commitment, to the company overall and to their profession, is predicated on a favorable evaluation of their jobs. Theoretical Contribution/Originality: This research provides new insight into how transformational leadership, work environment, and job satisfaction influence employee organizational commitment Keywords: Transformational Leadership; Work Environment; Job Satisfaction; Organizational Commitment.